(untitled) (African Human Mobility Review, 2025)
This study reviews the governance of Kampala’s food system and refugee protection approach in order to propose strategies to recognize and protect the food security needs of Kampala’s refugee population more effectively. Uganda is Africa’s largest refugee host, with a policy approach that has been widely lauded for its flexible settlement provisions and commitment to durable solutions. However, growing refugee populations and underfunding have led to serious pressures, severely exacerbated during the COVID-19 pandemic. One unique aspect of Uganda’s refugee governance approach is the allowance of refugee populations to self-settle outside of designated camps in the capital city, Kampala. This research uses a governance lens to explore what is being done to support the food security of this group, by whom, and how this could be improved. The researcher conducted interviews with asylum seekers and refugees living in two of Kampala’s large informal settlements (Kisenyi II and Namuwongo) and with a range of policy stakeholders during May 2023. Multiple levels of government and non-governmental organizations (NGOs) offer overlapping formal and informal services and programs accessible to different populations living in settlements. This paper points to gaps and limitations linked to resources, as well as difficulties identifying vulnerable populations, locating political responsibility, coordination, and weak policy implementation, and suggests governance strategies to respond better to refugee and asylum seekers’ food security needs. Key recommended responses are to overhaul the refugee registration system, recognize and protect urban food security, and improve policy actor coordination through collaborative strategies that move beyond awareness of the crisis to setting specific targets and timelines to address it.